ANALYSIS OF FACTORS THAT INFLUENCE THE IMPLEMENTATION OF TAX PLANNING IN SERVICE SERVICE SMEs REGISTERED AT PPJI REPRESENTATIVE BOARD NORTH SUMATERA - Suliani Suliani; Widya Astuty; Maya Sari (SEAN Institute, 2023)
Small and medium enterprises (SMEs) are people's businesses that support the economy. At the end of this pandemic period, the government is aggressively supporting MSMEs from capital assistance to reduce tariffs with the hope that in the future, apart from supporting the people's economy, SMEs can also support taxation in Indonesia. Of course, this must be accompanied by socialization of tax knowledge so that SMEs will be able to plan in the future for the progress of their business and good tax planning.This study examines the effect of tax administration, loopholes, tax rates and tax sanctions on the implementation of tax planning for micro, small and medium enterprises (SMEs) in catering services. This study analyzed the primary data of the questionnaire from 63 answers of SMEs respondents who were registered with PPJI, the North Sumatra Representative Council. Testing the research variables using the SmartPls 3.0 application. Tax administration, loopholes, tax rates and tax sanctions have a positive effect on the implementation of tax planning on SMEs. Most of the catering service SMEs registered with the PPJI North Sumatra Representative Council understand about taxation in Indonesia, but there are many other SMEs actors who do not understand taxation or do not get the latest information in the field of taxation. The results of the study are expected to be considered by the tax authorities to formulate future tax policies that can benefit both small and medium enterprises and the government.